Factorial Analysis on Flooded Soil Recovery using Soil Containing Arbuscular Mycorrhizal Fungi - N., Zainol; Nanthienie, Thangaperumal; Nur Hanisah, Zahari; Nor Hazwani, Aziz (2016)
This paper presents the factorial analysis on flooded soil (FS) recovery using soil containing Arbuscular Mycorrhizal fungi (SA) with the help of a selected host plant, Allium cepa L. (onion plant). In order to study the most contributing factor for the soil recovery, five factors were selected namely; pH of soil, water content, SA/FS ratio, light supply and depth of soil. This was to study the ability of SA to recover the nutrients (nitrogen, phosphorus and potassium) in the FS. Experimental design table was constructed using the concept of two level factorial by employing Design-Expert® software (Ver 7.1.6). Soil sample was collected after 12 days and analyzed for nitrogen, phosphorus and potassium concentrations using HACH Spectrophotometer. Later, the data was analyzed in the named software to determine the main effect of respective factors and interaction between factors. The results showed that water content, light supply and depth of soil were the important factors for nutrients recovery. The best condition for FS recovery using SA was at: pH of soil (4), water content (28 ml), SA/FS ratio (1:5), depth of soil (5 cm) and with light supply.